درجة امتلاك أساتذة التربية البدنية للكفاءة المعرفية في الحداثة الرياضية لمرحلة التعليم المتوسط - فرحاتي ، بوبكر; Supervisor :بركاتي ، نصر الدين (Mohamed Boudiaf University of M'Sila, 2025)
الملخص بالعربية(عبارة عن فقرة ): تهدف هذه الدراسة إلى معرفة درجة امتلاك أساتذة التربية البدنية والرياضية للكفاءة المعرفية في الحداثة الرياضية لدى تلاميذ التعليم المتوسط بمدينة مقرة، وذلك وفقًا لمتغيري الخبرة المهنية والمؤهل العلمي. اعتمدت الدراسة على المنهج الوصفي. تكونت عينة الدراسة من 64 أستاذًا تم اختيارهم بطريقة شاملة من مختلف متوسطاتبدائرة مقرة. تم استخدام استبيان مكون من 24 فقرة موزعة على ثلاثة محاور رئيسية: التدريب الرياضي، طرق التدريس، وقوانين الألعاب الرياضية. أشارت النتائج إلى أن الأساتذة يمتلكون مستوى متوسطًا من الكفاءة المعرفية في الحداثة الرياضية، مع وجود فروق دالة إحصائيًا تبعًا للمؤهل العلمي وسنوات الخبرة. وقد أوصت الدراسة بضرورة توفير تكوينات مستمرة وتحديث المناهج التعليمية بما يتماشى مع متطلبات الحداثة الرياضية. عنوان الدراسة : درجة امتلاك أساتذة التربية البدنية للكفاءة المعرفية في الحداثة الرياضية لمرحلة التعليم المتوسط  أهداف الدراسة :. التعرف على الفروق في الكفايات المعرفية لدى معلمي المرحلة الابتدائية في مجال تدريس حصة التربية البدنية والرياضية تبعًا لمتغيرات الجنس، الخبرة المهنية، والمؤهل العلمي.التساؤل العامالدراسة : ما مدى توافر الكفايات المعرفية لدى معلمي المرحلة الابتدائية في مجال تدريس حصة التربية البدنية والرياضية، والفروق تبعًا لمتغيرات الجنس، الخبرة المهنية، والمؤهل العلمي؟  التساؤلات الجزئية :  ما درجة امتلاك أساتذة التربية البدنية والرياضية لمرحلة التعليم المتوسط للكفاءة المعرفية في الحداثة الرياضية ؟  هل توجد فروق ذات دلالة إحصائية في درجة امتلاك أساتذة التربية البدنية والرياضية لمرحلة التعليم المتوسط للكفاءة المعرفية في الحداثة الرياضية تبعًا لمتغير سنوات الخبرة؟  هل توجد فروق ذات دلالة إحصائية في درجة امتلاك أساتذة التربية البدنية والرياضية لمرحلة التعليم المتوسط للكفاءة المعرفية في الحداثة الرياضية تبعًا لمتغير المؤهل العلمي؟ الفرضية العامةللدراسة :معرفة درجة امتلاك معلمي التربية الرياضية للكفاءة المعرفية في الحداثة الرياضية في مدينة المسيلة الفرضيات الجزئية :  يمتلك أساتذة التربية البدنية والرياضية لمرحلة التعليم المتوسطمستوى متوسط من الكفاءة المعرفية في الحداثة الرياضية.  توجد فروق ذات دلالة إحصائية في درجة امتلاك أساتذة التربية البدنية والرياضية لمرحلة التعليم المتوسط للكفاءة المعرفية في الحداثة الرياضية تبعًا لمتغير سنوات الخبرة.  توجد فروق ذات دلالة إحصائية في درجة امتلاك أساتذة التربية البدنية والرياضية لمرحلة التعليم المتوسط للكفاءة المعرفية في الحداثة الرياضية تبعًا لمتغير المؤهل العلمي. المنهج المتبع في الدراسة : المنهج الوصفي التحليلي الأدوات المستخدمة في الدراسة : المسح الشامل الكلمات المفتاحية الكفاءة المعرفية، الحداثة الرياضية، التربية البدنية جاءهذاالبحثفيفصول . الفصلالأول:الاطار العام للدراسة وتناولالفصلالثاني:الكفاءة المعرفية في الحداثة الرياضية أماالفصلالثالثأستاذ التربية البدنية والرياضية الفصلالرابع: الإجراءات المنهجية للدراسة الفصل الخامس: عرض النتائج ومناقشتها منأهمالنتائجالتيتوصلإليهاالباحث : يمتلك أساتذة التربية البدنية والرياضية لمرحلة التعليم المتوسط مستوى متوسط من الكفاءة المعرفية في الحداثة الرياضية أهم التوصيات:  برمجة دورات تدريبية منتظمة لأساتذة التربية البدنية والرياضية حول مستجدات الحداثة الرياضية، تشمل مجالات التدريب الحديث، القوانين الجديدة، وطرق التدريس النشطة، لتعزيز كفاءتهم المعرفية بشكل مستمر.  تطوير برامج التكوين الجامعي لطلبة معاهد التربية البدنية، من خلال إدراج وحدات دراسية تُعنى بالحداثة الرياضية والتكنولوجيا في التعليم الرياضي، مما يضمن إعداد أساتذة أكثر مواكبة.  تشجيع استخدام الوسائل الرقمية (مثل الفيديوهات التعليمية، الواقع الافتراضي، تحليل الأداء الرياضي) في حصص التربية البدنية، بما يعزز البعد التطبيقي للكفاءة المعرفية الحديثة.  إنشاء منصة وطنية مخصصة لأساتذة التربية البدنية، تسمح بتبادل التجارب والمصادر العلمية الحديثة في ميدان التربية البدنية والرياضية، وتُساهم في التشبيك المهني بينهم.  من المفيد ربط مسار ترقية أساتذة التربية البدنية بالمشاركة الفعلية في التكوينات المتخصصة في الحداثة الرياضية، لتحفيزهم على تطوير قدراتهم ومواكبة التحولات في الميدان. Searchlight in English Faculty Institute of Sciences and Sports and Technical and PhysicalActivities Department: Order No: No. d 'registration : Searcher :farhatiBoubaker Publicly supported on : Title of the thesis (dissertation): The degree of physical education teachers' cognitive competence in sports modernity at the intermediate level. Language of the thesis:Arab Model of the thesis: Master Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor:barkatinacereddine Grade: Lecturer Number of pages:71 pages Option: Summary : This study aims to identify the degree to which physical education teachers at the middle school level in the town of Maqra possess cognitive competence in sports modernity, based on the variables of teaching experience and academic qualification. The descriptive methodwas adopted as it best suits the analysis of the existing reality. The study sample consisted of 64 male and female teachers selected comprehensively from various educational institutions in the municipality. A questionnaire of 24 itemswas used, distributed across three main axes: sports training, teaching methods, and sports game rules. The results indicated that teachers possess a moderate level of cognitive competence in sports modernity, with statistically significant differences based on academic qualification and years of experience. The study recommended continuous training programs and updating educational curricula to align with the requirements of modern sports. Title of the study: A field study in the intermediate schools of the magradistrict. The purpose of the study: These studies aim to determine the degree to which physical education teachers possess cognitive competence in sports modernity in the city of M'Sila. Problem: 1- To whatextent do middle schoolphysicaleducation and sports teacherspossess cognitive competence in sports modernity? 2- Are therestatisticallysignificantdifferences in the degree of cognitive competence in sports modernityamong middle schoolphysicaleducation and sports teachersbased on the variable of years of experience? 3-Are therestatisticallysignificantdifferences in the degree of cognitive competence in sports modernityamong middle schoolphysicaleducation and sports teachersbased on the variable of academic qualification? Hypotheses: 1-Middle school physical education and sports teachers possess an average level of cognitive competence in sports modernity. 2- There are statistically significant differences in the degree of cognitive competence of middle school physical education and sports teachers in sports modernity according to the variable of years of experience. 3-There are statistically significant differences in the degree of cognitive competence of middle school physical education and sports teachers in sports modernity according to the variable of academic qualification. Key words :Cognitive competence, Sports modernity, Physical education - The most important results achieved are: Schedule regular training courses for physical education and sports teachers on the latest developments in sports innovation, including areas of modern training, new laws, and active teaching methods, to continuously enhance their cognitive competence. 1-Develop university training programs for students at physical education institutes by incorporating study modules focused on sports innovation and technology in sports education, ensuring the development of more up-to-date teachers. 2-Encourage the use of digital tools (such as educational videos, virtual reality, and sports performance analysis) in physical education classes, enhancing the practical dimension of modern cognitive competence. 3- Establish a national platform dedicated to physical education teachers, allowing for the exchange of experiences and modern scientific sources in the field of physical education and sports, and contributing to professional networking among them. 4-It is beneficial to link the promotion process for physical education teachers to actual participation in specialized training in sports innovation, to motivate them to develop their capabilities and keep pace with transformations in the field.
Keywords: الكفاءة المعرفية; الحداثة الرياضية; التربية البدنية